PENGARUH VARIASI PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DI KOPI NAKO YASMIN BOGOR - Nida Syifa Syauqiah; Ahmad Nurhadi (Journal of Research and Publication Innovation, 2024)
This study aims to determine the Influence of Product Variety and Service Quality on Consumer Satisfaction at Nako Yasmin Coffee Bogor both partially and simultaneously. The method used is a causal associative method with a quantitative approach with a sampel 96 respondents where the data was processed using the SPSS 26 application. The result of this study is that there is a positive and significant influence between product variations on consumer satisfaction in Nako Yasmin Bogor Coffee, this can be proven from the simple linear regression equation Y=1,450+0,734X1. The correlation value of the product variation variable was 0.753 which means that the level of relationship is strong. The value of the determination coefficient was 56.7%. The Hypothesis Test was assessed at 11,101 > 2,366. There is a positive and significant influence between service quality and consumer satisfaction in Nako Yasmin Coffee Bogor, which can be proven from the simple linear regression equation Y=2.538+0.525X2. The correlation value of the service quality variable was 0.835, which means that the level of relationship is strong. The value of the determination coefficient was 69.7%. The Hypothesis Test was assessed as 14,712 > 2,366. Simultaneously there is a positive and significant influence between product variation and service quality on consumer satisfaction in Nako Yasmin Coffee Bogor, this can be proven from the multiple linear regression equation Y=1.232+0.277X1+0.390X2, The correlation value of the service quality variable is 0.855 which means very strong. The value of the determination coefficient was 73.2%. As well as the Hypothesis Test, the value of Fcal was obtained 126.838 > Ftable 6.92.